ANALISIS DAN TIPEPASANG SURUT PERAIRAN PULAU JEMUR RIAU - Musrifin Musrifin (Berkala Perikanan Terubuk, 2012)
Tidal analyzedhave been conducted at PulauJemur waters. Fortnightlytidal range was measured by peil-schall. Harmonic Admiralty analyzed wasapplied to find out the Formzahlnumber.Average tidal range was 2,7 meters, meanlow water level (MLWL) 0,44 meters and mean high water level (MHWL) was4,97 meter. The hihgest tidal waters was 5,3 meters and the lowest was 0,0 meter.Based on Formzahlnumber F = 0,17 the type of tidal is semidiurnal. Flood andebb tide occur twice a day where one tidal range is similar in height from theother.